Cystic fibrosis transmembrane conductance regulator (CFTR): Making an ion channel out of an active transporter structure. Issue 1 (1st January 2018) - Linsdell, Paul
ABSTRACT: Cystic fibrosis is caused by mutations in the cystic fibrosis transmembrane conductance regulator (CFTR). CFTR is a member of the ATP-binding cassette (ABC) family of membrane transport proteins, most members of which function as ATP-dependent pumps. CFTR is unique among human ABC proteins in functioning not as a pump, but as an ion channel. Recent structural data has indicated that CFTR shares broadly similar overall architecture and ATP-dependent conformational changes as other ABC proteins. Functional investigations suggest that CFTR has a unique open portal connecting the cytoplasm to the transmembrane channel pore, that allows for a continuous pathway for Cl − ions to cross the membrane in one conformation. This lateral portal may be what allows CFTR to function as an ion channel rather than as a pump, suggesting a plausible mechanism by which channel function may have evolved in CFTR.